Vocabulary learning strategies: differences between Arabic and non-Arabic majoring students at the International Islamic University Malaysia - Muhd Isa, Rabiatul Aribah; Mustapha, Nik Hanan; Tg Abdul Rahman, Tg Ainul Farha; Abdul Pisal, Nadhilah (IDOSI Publications, 2014)
Previous studies conducted in the field of learning AFL or ASL, especially in Malaysia, have found that the most frequent problem faced by learners is vocabulary learning. Consequently, vocabulary learning strategies (VLS) have proven to be one of the solutions to this problem. Studies have been carried out on VLS among Arabic learners. However, these studies are restricted to learners majoring in Arabic, leaving the non-Arabic majors out. Thus, this study aims to investigate the vocabulary learning strategies used by Arabic and non-Arabic majors at the International Islamic University Malaysia. A sample of 311 students from both groups answered the ‘Vocabulary Learning Strategies Questionnaire’ by Takac (2008). The study found no significant difference between the Arabic and non-Arabic majors and the spontaneous strategies. Several implications are discussed in light of the results.